Cheese Analog Basis Susu Jagung Manis dan Susu Kedelai Sebagai Keju Rendah Lemak - Daulima, Dian Triana; Andriyani, Ade; Mustofa, Prayoga Nurul; Liputo, Siti Aisa (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
The purpose of this study is to produce analog chees from sweet corn milk and soy beans with lower fat levels than cheese in general. This study uses a randomized design with a single factor in 3 treatments that is the manufacture of analogue of sweet corn milk and mily soil with the addition of lactic acid bacteria with 1%, 2%, and 3% concentration. The observed parameters include physical characteristics (texture, color, scent and taste) and chemical (protein and fat content). The results showed that analogical cheese physical characteristics have soft texture, yellow pale color, slightly scaved aroma and salt taste. The results of protein analysis ranged from 8,42% - 10,90% and fat 2,41% - 3,60%. The analogue of the analog cheese in this study can be categorized low fat cheats than the cheese from animal milk.